2018
DOI: 10.1007/s40279-017-0832-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Interventions Designed to Improve Athletic Performance and Recovery: A Systematic Review of Current Approaches

Abstract: Future researchers should aim to conduct sleep interventions among different athlete populations, compare results, and further establish guidelines and intervention tools for athletes to address their specific sleep demands and disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
147
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 56 publications
(87 reference statements)
3
147
1
4
Order By: Relevance
“…There is contradictory evidence for which threshold (ie, medium vs high) is most appropriate for athletes17 39; therefore, research should explore how athlete type (ie, endurance vs power) and training phase (heavy vs light) affect bias of different thresholds 39. Moreover, while it is important to develop strategies that can mitigate sleep disturbances (eg, sleep hygiene) with the aim of improving performance,6 more objective data are required to better understand which athletes will benefit and when they will benefit from such strategies. For instance, despite reports that individual sport, aesthetic sport and female athletes are susceptible to sleep disturbances before competition,94 there are limited supportive, objective data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is contradictory evidence for which threshold (ie, medium vs high) is most appropriate for athletes17 39; therefore, research should explore how athlete type (ie, endurance vs power) and training phase (heavy vs light) affect bias of different thresholds 39. Moreover, while it is important to develop strategies that can mitigate sleep disturbances (eg, sleep hygiene) with the aim of improving performance,6 more objective data are required to better understand which athletes will benefit and when they will benefit from such strategies. For instance, despite reports that individual sport, aesthetic sport and female athletes are susceptible to sleep disturbances before competition,94 there are limited supportive, objective data.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, many athletes identify sleep as the most important recovery behaviour for athletic success 5. Extending sleep may be beneficial for sports-specific skill execution 6. Nightly sleep duration has been positively correlated with team netball performance7 and associated with injury risk in adolescent athletes 8…”
Section: Introductionmentioning
confidence: 99%
“…Given that burnout symptoms predict insomnia symptoms, the question of how we can prevent sleep complaints among young elite athletes, especially among athletes who perceive high levels of burnout, arises. A recent systematic review showed that research in this area is still in an early stage (Bonnar, Bartel, Koakoschke, & Lang, 2018). Based on ten existing intervention studies aimed at increasing performance and/or recovery through sleep interventions, Bonnar et al (2018) concluded that sleep extension was the most beneficial approach, whereas napping, sleep hygiene and post-exercise recovery strategies produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that research in this area is still in an early stage (Bonnar, Bartel, Koakoschke, & Lang, 2018). Based on ten existing intervention studies aimed at increasing performance and/or recovery through sleep interventions, Bonnar et al (2018) concluded that sleep extension was the most beneficial approach, whereas napping, sleep hygiene and post-exercise recovery strategies produced mixed results. Their review also suggests that sleep disturbances often occur during regular training periods due to poor sleep hygiene (e.g., late training or game sessions) or as a response to heavy training workloads (e.g., functional over-reaching).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation